The quest for 'Newness' in Jazz: implications of cage's relationship with Jazz - Chan, Cheong Jan (Tanjong Malim, 2013)
The quest for 'Newness' in Jazz: implications of cage's relationship with Jazz by Chan, Cheong Jan